Mengajar Siswa Tingkat Dasar dalam Menuju Smart Village di Desa Cemagi, Kabupaten Badung, Bali - Anak Agung Ketut Sri Asih; Komang Fridagustina Adnantara; Sarita Vania Clarisa; Gusti Ayu Putu Manik Yulia Pramita; Francise Connie Angelina Gunawan (Prosiding Seminar Nasional Riset dan Pengabdian pada Masyarakat, 2024)
The program of teaching elementary school students is one of the efforts by students to implement the Tri Dharma of Higher Education by contributing to the community. Triatma Mulya University organizes activities in Cemagi Village, Badung Regency, Bali, with the theme "Development of Community-Based Village Potential Towards a Smart Village", focusing on the Elementary School Teaching Program towards a Smart Village, particularly in building an excellent generation through quality education. Through qualitative descriptive methods, students are involved in teaching elementary school students at several schools, such as TK Waruna Kumara 1 Cemagi, SD Negeri 1 Cemagi, and SMA Negeri 2 Mengwi. This activity not only emphasizes academic aspects but also stimulates students' creativity through activities such as coloring competitions. The organization of a Seminar on Tips for Continuing to Higher Education for High School Students at SMA Negeri 2 Mengwi is also part of this activity, providing information and guidance to students about higher education. The success of this activity is evident from the participation that exceeds the target and the enthusiasm of students in participating in the activities. Overall, the activities in Cemagi Village not only benefit the local community but also provide a platform for students to apply the knowledge and skills they have acquired and contribute positively to community development as a whole.